EVALUASI PENGELOLAAN PENGGUNAAN DANA DESA (STUDI KASUS MENGENAI DANA DESA DI KECAMATAN KUTOARJO) - , (Politeknik Sawunggalih Aji, 2022)
The Indonesian government relies on allocation of transfers to the regions and village funds in developing Indonesia. In an effort to build a village, issued Law No. 6 of 2014 to regulate the Village Fund program. Since the commencement of the Village Fund program, the government and the community expressed so much hope that among them is to maintain and increase people's purchasing power and to build infrastructure and labor-intensive sectors that can directly impact the economy and welfare of rural communities The purpose of this study was to determine how the management of village funds uses 4 dimensions, namely the dimensions of financial management, dimensions of infrastructure and development, dimensions of community empowerment, and dimensions of fraud The results showed that in the first dimension of Kutoarjo Subdistrict all respondents chose A1, A2 and A3 points followed by A6, A5, A4. In the Village Infrastructure Development dimension, it appears that the Village Fund tends to be focused on funding the construction for agricultural business production for food security and agricultural business. In the dimension of Community Empowerment the villages studied noted that the empowerment program was used to manage village information and communication facilities and infrastructure. In the Dimension of Fraud it was recorded that there were no villages using the Village Fund to fund programs that were not prioritized or included in existing provisions